2019
DOI: 10.1055/s-0039-1697605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Mucolipidoses II and III: A Multicenter Study

Abstract: Mucolipidoses (MLs) II and III are rare lysosomal diseases caused by deficiency of GlcNAc-1-phosphotransferase, and clinical manifestations are multisystemic. Clinical and demographic data from 1983 to 2013 were obtained retrospectively. Twenty-seven patients were included (ML II = 15, ML III α/beta = 9, ML III gamma = 3). The median age at diagnosis was 2.7 years. The predominant clinical presentations were skeletal symptoms. The ML II patients showed physical and cognitive impairment, while the ML III α/beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, not only patients with cervical spine pathologies need special attention, but also those with lower vertebral column abnormalities, which are also common in ML. The frequency of MLII children with thoracolumbar gibbus abnormality in this study (57%) roughly equals the percentage reported by Alegra et al (50%) [29]. The literature contains a number of reports on children with MPS with neurological sequels after anaesthesia [10], such as an MPS IH patient with a 76 • thoracic kyphosis and irreversible paraplegia after extremity surgery [30].…”
Section: Discussionsupporting
confidence: 77%
“…However, not only patients with cervical spine pathologies need special attention, but also those with lower vertebral column abnormalities, which are also common in ML. The frequency of MLII children with thoracolumbar gibbus abnormality in this study (57%) roughly equals the percentage reported by Alegra et al (50%) [29]. The literature contains a number of reports on children with MPS with neurological sequels after anaesthesia [10], such as an MPS IH patient with a 76 • thoracic kyphosis and irreversible paraplegia after extremity surgery [30].…”
Section: Discussionsupporting
confidence: 77%
“…Frequently described hip pathologies in MLII patients are dysplasia and dislocation, however, the current literature lacks exact pathological differentiation and classification [6,[23][24][25][26]. Ocada et al documented congenital dislocation of hip joints in 10/14 Japanese MLII patients without mentioning, how dislocation was diagnosed or whether both sides were affected [25].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six patients included in this study have already been described in the literature [5,[14][15][16][17][18]. Four patients are described herein for the first time (P29 to 32).…”
Section: Patientsmentioning
confidence: 99%
“…Compared to MLII, the disease progression is slower and life expectancy is longer. ML III gamma (MIM #252605) is caused only by pathogenic variants in the GNPTG gene and presents as the milder disease, with joints and bone symptoms and average life expectancy [1,4,5].…”
Section: Introductionmentioning
confidence: 99%